THE ROLE OF DYNAMIC SYSTEMS THEORY IN THE USE OF ALTERNATIVE ENERGY SOURCES (KIUT Publication, 2025)
Using the theory of dynamic systems is of great importance for improving the efficiency of alternative energy sources. This article presents an analysis of solar, wind, and bioenergy systems based on dynamic models.